New concepts of the supplementary motor area - Tanji, Jun (Current opinion in neurobiology, 1996)
The supplementary motor area, although traditionally defined as a single motor area, is not viewed as including at least three different areas that can be distinguished anatomically and physiologically. The differential use of these three areas for various motor behaviors has been the subject of recent studies that are beginning to provide novel concepts of the functional differentiation of each area.